(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The study aims to indicate the role of the agricultural initiative in building agricultural development, mediated by activation of the role of internal and external audit on agricultural initiative projects, for the purpose of meeting the challenges of abuses on agricultural land and lack of water used in agriculture and proportions of high poverty, which led to the rural people of the migration to the city and leave agriculture and livestock, and that of the main conclusions reached by the researcher. When comparing the work of the external auditing agencies (the Federal Office of Financial Supervision) on the initiative of agricultural projects with internal audit services in the Directorate of Agriculture and branches of the Agricultural Cooperative Bank in the province observed not to activate the internal audit services in the Directorate of Agriculture in agricultural development, the researcher recommended to maintain the agricultural initiative projects stop and neglect mediated oversight and provide ongoing support to them for these projects from the role in agricultural development.